Agonist-Mediated Activation of STING Induces Apoptosis in Malignant B Cells - Tang, Chih-Hang Anthony; Zundell, Joseph A; Ranatunga, Sujeewa; Lin, Cindy; Nefedova, Yulia; Del Valle, Juan R; Hu, Chih-Chi Andrew (Cancer research (Chicago, Ill.), 2016)
Endoplasmic reticulum (ER) stress responses through the IRE-1/XBP-1 pathway are required for the function of STING (TMEM173), an ER-resident transmembrane protein critical for cytoplasmic DNA sensing, IFN production, and cancer control. Here we show that the IRE-1/XBP-1 pathway functions downstream of STING and that STING agonists selectively trigger mitochondria-mediated apoptosis in normal and malignant B cells. Upon stimulation, STING was degraded less efficiently in B cells, implying that prolonged activation of STING can lead to apoptosis. Transient activation of the IRE-1/XBP-1 pathway partially protected agonist-stimulated malignant B cells from undergoing apoptosis. In Eμ-TCL1 mice with chronic lymphocytic leukemia, injection of the STING agonist 3'3'-cGAMP induced apoptosis and tumor regression. Similarly efficacious effects were elicited by 3'3'-cGAMP injection in syngeneic or immunodeficient mice grafted with multiple myeloma. Thus, in addition to their established ability to boost antitumoral immune responses, STING agonists can also directly eradicate malignant B cells. Cancer Res; 76(8); 2137-52. ©2016 AACR.